Native Pathways to Science, Technology, Engineering, and Math Graduate Degrees. Issue 187 (9th September 2019) - Mills, Jack I.; Thomas, Aaron; Galindo, Ed; Hartline, Beverly Karplus; Dhingra, Amit
Abstract: There is a pressing need for American Indian and Native Alaskan professionals who have the preparation necessary to address the quality of life and natural resource issues in Native communities. We assert that universities should adopt proactive strategies that build pathways for Natives to obtain advanced degrees.